1994
DOI: 10.1002/j.1460-2075.1994.tb06649.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidasin: a novel enzyme-matrix protein of Drosophila development.

Abstract: Peroxidasin is a novel protein combining peroxidase and extracellular matrix motifs. Hemocytes differentiate early from head mesoderm, make peroxidasin and later phagocytose apoptotic cells. As hemocytes spread throughout the embryo, they synthesize extracellular matrix and peroxidasin, incorporating it into completed basement membranes. Cultured cells secrete peroxidasin; it occurs in larvae and adults. Each 1512 residue chain of the three‐armed, disulfide‐linked homotrimer combines a peroxidase domain with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
208
2
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(223 citation statements)
references
References 48 publications
4
208
2
4
Order By: Relevance
“…Close to its C-terminus, the Drosophila PXDN contains an amphipatic -helical region, which was proposed to form homotrimeric coiled coil (6). A homologous region between amino acids 1383 and 1411 is also recognizable in the mammalian protein and we assume that trimerization via this region positions the C736 and C1315 residues to form intermolecular disulfide bonds leading to the assembly of a stabilized PXDN trimer.…”
Section: Discussionmentioning
confidence: 95%
“…Close to its C-terminus, the Drosophila PXDN contains an amphipatic -helical region, which was proposed to form homotrimeric coiled coil (6). A homologous region between amino acids 1383 and 1411 is also recognizable in the mammalian protein and we assume that trimerization via this region positions the C736 and C1315 residues to form intermolecular disulfide bonds leading to the assembly of a stabilized PXDN trimer.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, another possible function of the 120-kDa protein is recognition of the extracellular matrix of larval tissues, which leads to tissue disintegration. It has been shown that scavenger receptors are implicated in cell±matrix interactions, suggesting this possibility [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The trimeric Drosophila protein peroxidasin has also been found to contain a procollagen module near its proposed oligomerization site (54). TSP1 lacking C was primarily expressed as dimers and monomers by mouse NIH 3T3 cells (13).…”
Section: Table IIImentioning
confidence: 99%